Further development of the MRONJ minipig large animal model. Issue 9 (September 2017) - Otto, Sven; Pautke, Christoph; Martin Jurado, Olga; Nehrbass, Dirk; Stoddart, Martin J.; Ehrenfeld, Michael; Zeiter, Stephan
Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a rare but serious and potentially severe side effect of antiresorptive therapy with bisphosphonates or denosumab. Recently, a large animal minipig MRONJ model was introduced which led to early necrotic lesions in the majority of extraction sites after bisphosphonate administration. The aim of this project was to modify the preoperative cumulative bisphosphonate dose (zoledronate) and hereby firstly to demonstrate the reliability and reproducibility of the established model. Secondly, the MRONJ lesions should be carefully investigated using clinical and μCT as well as detailed histological analyses. Twelve 1.5-year-old Göttingen minipigs were divided into three groups. In group 1 (n = 3) minipigs received weekly doses of zoledronate intravenously (0.05 mg/kg bodyweight) for 20 weeks. No interventions were performed. In group 2 (n = 6) animals received the identical zoledronate dosage as animals in group 1 and tooth extractions of two premolars (PM 2 and 4) in each jaw (maxilla and mandible) were performed after 12 weeks. Group 3 (n = 3) served as tooth extraction only control (no zoledronate administrations). The jaw-bones were subjected to detailed macroscopic, radiological and histological investigations. All extraction sites (24/24) in animals of group 2 showed clinical, radiological and histological signs of MRONJ (mainly stage II), whereas no bone necrosis was found in group 3. Animals of group 1 and group 2 showed further MRONJ lesions in areas where infections (periodontitis) were present. This is the first large animal model to show a 100% incidence of MRONJ at all extraction sites in bisphosphonate pretreated animals (group 2). In addition, in this preclinical model for MRONJ it is shown that tooth extractions are not mandatory for a MRONJ manifestation. MRONJ also developed in areas of gingival or periodontal infections. Highlights: The paper presents a reliable and very robust large animal model for MRONJ. The dosing of zoledronate (0.05 mg/kg bodyweight) closely resembles the oncological setting in humans. After pretreatment with zoledronate and tooth extractions without preventive measurements MRONJ lesions developed at all extraction sites in 6 of 6 animals and 24 of 24 extraction sites. There were also further MRONJ lesions in areas of local infections especially marginal periodontitis and food entrapment further stressing the role of infection in the pathogenesis of MRONJ.